Disaster Communication in Local Governments Karangasem Regency, Bali Indonesia to Realize Sustainable Tourism - Nurjanah, Adhianty (Universitas Syiah Kuala, 2025)
This research aims to examine disaster communication In Karangasem Regency Bali Indonesia to realize sustainable tourism. The development of quality tourism is very necessary for national economic development, considering that tourism makes a major contribution to the economy of a country, especially in Bali which is an ODTW in Indonesia. Karangasem Regency has great potential in developing sustainable tourism. This study uses a qualitative descriptive method with a case study approach. The research location is in Karangasem Regency, Bali. The data were collected through in-depth interviews with relevant stakeholders and the government officials such as the Tourism Office and Regional Disaster Management Agency (BPBD) of Karangasem Regency. The secondary data of this research is sourced from policy documents, disaster risk communication guidelines, and disaster incident reportsThe results of the study show that disaster communication in Karangasem Regency Bali is carried out by BPBD Karangasem in collaboration with the community and tourism managers to convey disaster information to the community and tourists. However, it is necessary to improve coordination between the Tourism Office and BPBD and increase tourists' understanding of disaster risks to support the realization of sustainable tourism.